2021
DOI: 10.1155/2021/1479201
|View full text |Cite
|
Sign up to set email alerts
|

Deep Neck Infection: Atypical Presentation of Papillary Thyroid Cancer

Abstract: Deep neck infection is defined as an infectious process in the potential spaces and fascial plane of the neck which may result in a fatal complication. Prompt drainage and broad-spectrum antibiotics are the mainstays of treatment. Deep neck infection as the initial presentation of primary head and neck cancer is not common. Nevertheless, head and neck squamous cell carcinoma is the most common primary head and neck cancer, which could present with cervical metastasis and subsequently becomes infected. Papillar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 10 publications
(17 reference statements)
0
3
0
Order By: Relevance
“…Even the rare similar cases reported in the literature were thyroid carcinomas mimicking the presentation of cervical abscess rather than tuberculosis [4,5,6]. In fact, Loh TL et al [4] reported a rare case in 2018 of anaplastic thyroid carcinoma mimicking a thyroid abscess in a 52-year-old patient.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Even the rare similar cases reported in the literature were thyroid carcinomas mimicking the presentation of cervical abscess rather than tuberculosis [4,5,6]. In fact, Loh TL et al [4] reported a rare case in 2018 of anaplastic thyroid carcinoma mimicking a thyroid abscess in a 52-year-old patient.…”
Section: Discussionmentioning
confidence: 97%
“…Mahattanapreut et Al. [5] Reported in 2021 a case 67-year-old patient presented with a large abscess involving the retropharyngeal space, oro-hypopharynx, larynx, and left lobe of the thyroid gland with multiple lymphadenopathies with cystic necrosis. The patient underwent incision and drainage of the abscess and necrotic tissue samples were sent for histopathology.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation